Systematics of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) - Nascimento, Jeane M. C. Do; Salles, Frederico F.; Hamada, Neusa (Zootaxa, 2017)
In the present paper, based on specimens from different regions of Brazil, we review the current knowledge of the Neotropical genus Simothraulopsis. A phylogenetic study was performed in order to address the relationships between all species and to test the monophyly of Simothraulopsis. For this purpose, 48 characters related to the external morphology of adults and nymphs were investigated. As a result, four new species are described; S. caliginosus sp.nov., S. dominguezi sp. nov., S. eurybasis sp. nov., S. inaequalis sp. nov. New taxonomic and biological information are added to this genus. Nymphs of S. diamantinensis Mariano, 2010 and S. janae Mariano, 2010 are described for the first time and several new distributional records for Brazil are provided. Additionally, keys for male imagos and nymphs of the genus are proposed. The phylogenetic analysis corroborated the monophyly of Simothraulopsis, however, the division in two subgenera as previously proposed was not recovered in our reconstruction.